The influence of teachers' intrinsic motivation on students' intrinsic motivation: The mediating role of teachers' motivating style and teacher‐student relationships - Zou, Honghui; Yao, Jihai; Zhang, Yuexin; Huang, Xinyi (Psychology in the schools, 2024)
Teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning are important contributors to effective teaching and learning, and exploring their relationships and influencing mechanisms can clarify the path to promote teachers' professional development and students' overall growth. In our study, 44 secondary school teachers and 2461 secondary school students completed questionnaires, and a multilevel structural equation model was used to explore the influence of teachers' intrinsic motivation for teaching on students' intrinsic motivation for learning and the mediating role of teachers' motivating style and teacher‐student relationships. The results showed that (1) teachers' intrinsic motivation for teaching was significantly positively correlated with students' intrinsic motivation for learning, and the former had a significant direct effect on the latter; (2) teachers' autonomy‐supporting motivating style, positive teacher‐student relationships, and negative teacher‐student relationships played mediating roles between teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning; and (3) teachers' motivating style and teacher‐student relationships played a chained mediating role between teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning. Practitioner points This research can clarify the path to promote teachers' professional development and students' overall growth. Teachers' intrinsic motivation for teaching had a significant direct effect on students' intrinsic motivation for learning. Teachers' motivating style and teacher‐student relationships played a chained mediating role between teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning.